The current state of financial and regulatory frameworks in Asian economics: The case of India - Abhijit Sen Gupta (Asian Development Bank Institute (ADBI), 2011)
Despite having a low exposure to the toxic assets involved in the sub-prime crisis and a gradualist approach towards liberalization of the financial sector, certain parts of the Indian financial sector were significantly affected by the global financial crisis. The consequent tightening of liquidity and slump in global and domestic demand had a strong adverse affect on the industrial sector, a large part of which includes small and medium-sized enterprises. There was a significant decline in employment and output in some of these enterprises. Though Indian policymakers reacted in a proactive manner and introduced a host of measures to counter the adverse effects of the financial crisis, the recovery has not been uniform; several markets and sectors are still reeling from the crisis' aftershocks. The proposed Basel III norms are going to have a significant impact on the Indian financial sector. While it is in a comfortable position to meet some of the proposed Basel III norms, the implementation of some of the other norms will be a challenge.
Keywords: F41; G15; O11; 330; Finanzmarktkrise; Finanzsektor; Makroökonomischer Einfluss; Kapitalmarktliberalisierung; Regulierung; Basel II; Indien